2007
DOI: 10.1162/jocn.2007.19.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Intermanual Differences in Movement-related Interhemispheric Inhibition

Abstract: Abstract& Interhemispheric inhibition (IHI) between motor cortical areas is thought to play a critical role in motor control and could influence manual dexterity. The purpose of this study was to investigate IHI preceding movements of the dominant and nondominant hands of healthy volunteers. Movement-related IHI was studied by means of a double-pulse transcranial magnetic stimulation protocol in right-handed individuals in a simple reaction time paradigm. IHI targeting the motor cortex contralateral (IHI c ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
163
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(186 citation statements)
references
References 72 publications
(137 reference statements)
18
163
1
Order By: Relevance
“…Recent work from Fujiyama et al (2012a, b) reports that an increased capacity to regulate inhibitory function was positively associated with better performance levels in older adults. It is noteworthy that previous studies already showed that preparatory suppression might be manifested at the cortical level, including inhibitory processes in the contralateral motor area (Duque et al 2007;Hinder et al 2010;Talelli et al 2008). Additionally, the involvement of higher order motor areas such as the dorsal premotor cortex cannot be ruled out (Duque et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Recent work from Fujiyama et al (2012a, b) reports that an increased capacity to regulate inhibitory function was positively associated with better performance levels in older adults. It is noteworthy that previous studies already showed that preparatory suppression might be manifested at the cortical level, including inhibitory processes in the contralateral motor area (Duque et al 2007;Hinder et al 2010;Talelli et al 2008). Additionally, the involvement of higher order motor areas such as the dorsal premotor cortex cannot be ruled out (Duque et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Also, magnetoencephalographic recordings of movement-related fields have demonstrated a bilateral activation of motor areas at about 500 ms prior to self-paced unilateral movements (Cheyne et al, 1991;Salmelin et al, 1995;Tandonnet et al, 2003). Nevertheless, previous TMS studies have yielded contradicting results showing that the excitability of the hemisphere ipsilateral to a movement was increased (Hoshiyama et al 1996;Muellbacher et al, 2000), decreased (Leocani et al, 2000;Duque et al, 2007) or unchanged during the performance of unilateral movements (MacKinnon and Rothwell, 2000). However, in a recent study Tandonnet et al (2010) showed that the amplitude of the MEP decreased for the ipsilateral motor cortex (corresponding to the non-responding hand in a choice reaction time paradigm) after 130 ms poststimulus presentation.…”
Section: Discussionmentioning
confidence: 99%
“…A second important limitation of this study is that these results are mainly based on the transcallosal modulation hypothesis, which has not been yet fully demonstrated and it should be taken carefully. In this context, inter-hemispheric inhibition measured through paired-pulse techniques between the right and the left primary motor areas (Duque et al, 2005;Duque et al, 2007;Vercauteren et al, 2008) might allow translating the increase (decrease) of MEP amplitudes measured following errors (correct) into a decrease (increase) of transcallosal suppression over the M1 contralateral to the responding hand. A third caveat corresponds to the lack of knowledge of the modulation of the excitability of the motor system measured by delivering pulses on the motor cortex contralateral to the active hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the two hemispheres is balanced by means of "silent" inhibition guaranteed by the fibres in the corpus callosum, and this inhibition process can be impaired as a consequence of stroke [34]. As an example, in finger movement tasks, the M1 area increases its inhibition towards the injured hemisphere through the connections of the corpus callosum causing a decrease in excitability [35]. Studies in patients after stroke reported an increase in M1 area activity and abnormal inhibition in the damaged part, resulting from an imbalance in activity between the two brain hemispheres [36].…”
Section: Neuroplasticity and Brain Repair After Strokementioning
confidence: 99%